2018
DOI: 10.3390/rs10121937
|View full text |Cite
|
Sign up to set email alerts
|

GPS Time Series Analysis from Aboa the Finnish Antarctic Research Station

Abstract: Continuous Global Positioning System (GPS) observations have been logged at the Finnish Antarctic research station (Aboa) since February 2003. The station is located in Dronning Maud Land, East Antarctica. Almost 5000 daily observation files have been archived based on yearly scientific expeditions. These files have not been fully analysed until now. This study reports for the first time on the consistent and homogeneous data processing and analysis of the 15-year long time series. Daily coordinates are obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…RTKLIB is widely used in navigation; for example, it can be used for automated machine guidance (AMG) and automated machine control (AMC) of mining vehicles [8], determination of position or trajectory of aircrafts [9], and navigation of marine vessels with IMU (Inertial measurement unit) [10]. RTKLIB’s PPP module can be applied to produce daily solutions for GPS time series analysis [11], and to evaluate the seismic waveforms and the co-seismic displacements derived by an earthquake [12]. Secondary development based on RTKLIB, GAMP utilizes the PPP algorithm to process multi-GNSS undifferenced and uncombined observations [13].…”
Section: Introductionmentioning
confidence: 99%
“…RTKLIB is widely used in navigation; for example, it can be used for automated machine guidance (AMG) and automated machine control (AMC) of mining vehicles [8], determination of position or trajectory of aircrafts [9], and navigation of marine vessels with IMU (Inertial measurement unit) [10]. RTKLIB’s PPP module can be applied to produce daily solutions for GPS time series analysis [11], and to evaluate the seismic waveforms and the co-seismic displacements derived by an earthquake [12]. Secondary development based on RTKLIB, GAMP utilizes the PPP algorithm to process multi-GNSS undifferenced and uncombined observations [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the North component of GOA_2 solution, power peaked at roughly 26-27 cpy, corresponding to the period of the ~14-day cycle. The 14-day cycle was observed in cGNSS timeseries previously [54]. It approximately follows the aliased period resulting from the unmodeled diurnal O1 and semidiurnal M2 tides [55].…”
Section: Noise Propertiesmentioning
confidence: 65%
“…In the North component of GOA_2 solution, power peaked at roughly 26-27 cpy, corresponding to the period of the~14-day cycle. The 14-day cycle was observed in cGNSS time-series previously [54].…”
Section: Noise Propertiesmentioning
confidence: 94%
“…Due to different measured data (such as global atmospheric pressure, ocean bottom pressure, land water reserves), different geophysical models and methods, the environmental loading displacement at the same stations obtained by the above institutions and softwares may be quite different. For example, Andrei et al (2018) calculated the 15-year coordinate time series of the Finnish Antarctic research station, namely ABOA, and compared the environmental loading products provided by GFZ, EOST and IMLS. The study found that the non-tidal oceanic loadings given by GFZ and EOST were signi cantly different.…”
Section: Introductionmentioning
confidence: 99%